Comparative Analysis of OHS Professional Certification Systems: A Scoping Review - Agung Raharjo; Januar Ariyanto; Farahul Jannah (Journal of Global Research in Public Health, 2026)
As Occupational Health and Safety (OHS) evolves into a sophisticated discipline, standardizing professional recognition is critical. This scoping review maps certification mechanisms and governance models to identify effective system components. A scoping review following Arksey and O'Malley's framework was conducted. Three databases (Scopus, Web of Science, CINAHL) and grey literature sources were searched in March 2026. Data were extracted and synthesized using narrative thematic analysis. Analyzing 30 sources from 1976 to 2024, we identify four governance models and a shift toward capability-based frameworks. Results indicate that effective systems utilize independent examinations and two-tier structures, whereas reliance on short-duration training or portfolio assessment risks limited professional capability. The review suggests that robust professionalization requires aligning education, examination, and governance, suggesting developing nations adopt rigorous, standardized assessment to ensure workforce capability.